PENGARUH PERFORMA LAPORAN KEUANGAN DAN MAKROEKONOMI TERHADAP HARGA SAHAM PERUSAHAAN TEKNOLOGI - Ravaes, Maulana Wafi; Silvi Asna Prestianawati (Contemporary Studies in Economic, Finance and Banking, 2023)
Stock price is one of the benchmarks of company performance, including technology companies. Various macro and micro factors can affect the stock price of technology companies, some of these factors are profitability, liquidity, solvency, inflation, and exchange rates. This study seeks to determine and analyse the effect of financial statement performance and macroeconomics on the stock prices of technology companies in Indonesia. This study uses panel data with 9 technology companies in Indonesia included in the IDXTECHNO industry classification during 2019-2021. The regression model used is panel data regression with hypothesis testing using t test, F test and coefficient of determination. The results showed that the performance of financial statements in the profitability dimension had a positive and significant effect, the liquidity dimension had a negative and insignificant effect, the solvency dimension had a positive and insignificant effect. and for macroeconomics in the exchange rate dimension had a negative and significant effect, the inflation dimension had a negative and insignificant effect. This indicates that the use of profitability and exchange rates can increase the share price of technology companies in Indonesia. Therefore, improving the performance of financial statements and economic stability should be further enhanced.